Tertiary English students’ attitude towards intercultural language learning - Morganna, Ruly; Sumardi, S.; Tarjana, Sri Samiati (Universitas Pendidikan Indonesia, 2020)
The nature of English as the world lingua franca and the nature of Indonesian students who are multicultural call for the application of Intercultural language learning (ILL) approach in English education in Indonesia. However, the complexities of ILL seem to demand English teachers’ positive attitude towards ILL even since they became tertiary English students so that ILL could be ideally implemented in the classroom. This study was conducted to delve into tertiary English students’ attitude towards ILL and to confirm their English teaching practices according to the perspective of ILL principles. Tertiary students taking English Education major at a State University in central Java were chosen to be the participants. Interview, questionnaire, and observation were deployed to garner the data. The findings demonstrated that most of the tertiary English students had a positive attitude towards ILL. Their judgments exhibited a positive tendency to accept and support ILL ideologies and principles. Their positive tendency covered three dimensions: affection (76.13%), cognition (75.08%), and behavior (75.16%). Observations showed that their English teaching practices tended to confirm their positive attitude towards ILL. They were able to apply three ILL principles consisting of active construction, making connection, and interaction. Other studies are expected to address ILL implementation in the formal English classrooms at Indonesian schools so that detailed merits and challenges as well as solutions with respect to ILL implementation can be revealed.